Derecho a la Presunción de Inocencia y su aplicación en el dictamen de Medidas de Protección en procesos de violencia contra la mujer y miembros del núcleo familiar - Cárdenas Casa, Edgar Patricio (2024)
The presumption of innocence is a right recognized under international Human Rights regulations; The Ecuadorian state, as a guarantor of rights, recognizes in its constitutional regulations due process and therein the presumption of innocence, until the contrary is proven in accordance with a final ruling. In the development of the legal investigation, the attribution to the conjecture of innocence of the denounced subject will be established, in the ruling and granting of protection measures, in crimes of violence against women or members of the family nucleus, under the protection of the that provides for due process. The methodology applied is qualitative, to allow the description, understanding, interpretation and justification of the legal phenomenon under study, presumption of innocence in the face of protection measures. Obtaining as a result the questioning of the constitutional right to due process in matters of evidence, right to defense, legal security and effective judicial protection; In legal practice, the right to jurisdiction that the accused person has. The procedure with which protection measures are applied, in their application, must be reformed.